(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Man’s quest for optimal level of health is a cultural universal across societies. This could be explained by the fact that good health is crucial both for man’s survival and his ability to meet set goals and aspirations in life. For man to live and function to his fullest capacities, use of health facilities is crucial. That is why the Cross River State government developed patterns of health services called “Ayadecare” to care for their people. This study adopted a survey research design which involves the collection of data to accurately and objectively describe existing phenomena. A sample size of 380 respondents was drawn through simple random sampling technique across the workers in the State Ministries. A self-administered questionnaire was used for the study. Data collected were inputted into Scientific Package for Social Sciences (SPSS) version 20. The results and discussion of the finding is presented using descriptive statistics. The study found out that the level of access to the scheme is not encouraging, and could be attributed to workers’ poor knowledge of the scheme and low awareness, which may be due to workers laxity in registering in the scheme. The study recommend that, there is need for public awareness to be created on the relevance of Ayadecare to people, communities and workers through social workers, community leaders, stakeholders and employers at work place